DICER Inactivation Identifies Pancreatic β-Cell “Disallowed” Genes Targeted by MicroRNAs - Martinez-Sanchez, Aida (Mol Endocrinol, 2015)
Pancreatic β-cells are the body's sole source of circulating insulin and essential for the maintenance of blood glucose homeostasis. Levels of up to 66 “disallowed” genes, which are strongly expressed and play housekeeping roles in most other mammalian tissues, are unusually low in β-cells. The molecular mechanisms involved in repressing these genes are largely unknown. Here, we explore the role in gene disallowance of microRNAs (miRNAs), a type of small noncoding RNAs that silence gene expression at the posttranscriptional level and are essential for β-cell development and function. To selectively deplete miRNAs from adult β-cells, the miRNA-processing enzyme DICER was inactivated by deletion of the RNase III domain with a tamoxifen-inducible Pdx1CreER transgene. In this model, β-cell dysfunction was apparent 2 weeks after recombination and preceded a decrease in insulin content and loss of β-cell mass. Of the 14 disallowed genes studied, quantitative RT-quantitative real-time PCR revealed that 6 genes (Fcgrt, Igfbp4, Maf, Oat, Pdgfra, and Slc16a1) were up-regulated (1.4- to 2.1-fold, P < .05) at this early stage. Expression of luciferase constructs bearing the 3′-untranslated regions of the corresponding mRNAs in wild-type or DICER-null β-cells demonstrated that Fcgrt, Oat, and Pdgfra are miRNA direct targets. We thus reveal a role for miRNAs in the regulation of disallowed genes in β-cells and provide evidence for a novel means through which noncoding RNAs control the functional identity of these cells independently of actions on β-cell mass.